Menstrual characteristics of adolescent athletes: a study from West Bengal, India - Mukherjee, P.; Mishra, S. K.; Ray, S. (Collegium Antropologicum, 2014)
The present study investigates: (i) differences in menstrual characteristics of athlete and non-athlete adolescents; (ii) relationship between menstrual characteristics, anthropometric variables, athletic status and socioeconomic status. The present study was conducted among 159 unmarried adolescents (80 non-athletes and 79 athletes) of age 15 to 19 years. The study participants belong to Bengali speaking Hindu ethnic group of Kolkata, the capital city of West Bengal State of India. Data were collected on socio-demographic and menstrual characteristics using pre-tested questionnaires. Anthropometric measurements were taken following standard methods. Descriptive statistics were used to understand the differences in menstrual characteristics between athletes and non-athletes, stepwise linear regression analyses were carried out to predict age at menarche, menstrual cycle length and duration of menstrual discharge using socio-demographic and anthropometric variables as well as athletic status as independent variables. Logistic (binary) regression was carried out to assess the strength of association between menstrual characteristics (as dependent variables) and athletic status, socio-demographic and anthropometric variables, and other menstrual characteristics (independent variables). The study participants differ significantly (p < or = 0.05) for certain menstrual characteristics such as age at menarche, cycle length, skipped cycle, premenstrual syndrome, heavy discharge when compared for their athletic status. Certain anthropometric and socioeconomic variables were found to be significantly associated with their menstrual characteristics. The study results demonstrate that menstrual functioning among adolescents is significantly influenced by their athletic status. The findings of this study would help health care professionals to devise future health care programs for adolescents in general and athletes in particular.